Investigation of the spatial and temporal long-term hydro-climatic trends in Upper Omo Gibe Basin, Ethiopia - Eyasu Tafese Mekuria; Tamene Adugna Demissie; Fekadu Fufa Feyessa (Heliyon)
Human activities have changed hydroclimatic components worldwide, affecting agricultural productivity and water resources management. This research examined the spatial and temporal variability of hydroclimatic variables in the Upper Omo Gibe Basin. Modified Mann-Kendall, Senʼs slope, and Innovative Trend Analysis methods were used to study the trends. The maximum statistically significant increasing trend of rainfall (P < 0.05) was observed at Limugenet station (Z = 3.641, S = 16.484), and a decreasing trend of rainfall was observed in Dedo station (Z = −2.732, S = −31.099). A generally decreasing rainfall trend was observed in the Upper Omo Gibe Basin. Temperature showed an upward trend in seasonal and annual observation. In spring, summer, autumn, and winter seasons the maximum significantly increasing trend (P < 0.05) of maximum temperature was 0.25 oC/year, 0.15 oC/year, 0.043 oC/year, and 0.082 oC/year respectively whereas the annual maximum significantly increasing trend was 0.083 oC/year. A significant increase in streamflow (P < 0.05) was observed at the Gibe gauging station (Z = 2.02) and Gilgel Gibe at Assendabo station (Z = 2.02) in the summer season. A significant decrease trend of streamflow has been observed in the Bulbul gauging station in the spring season (Z = −2.20), Megecha gauging station in the summer season (Z = −2.19), and annual (Z = −2.34). A statistically significant increasing and decreasing trend observed was 22 (27.5 %), 43 (53.75 %), 39 (48.75 %), and 5 (10 %) for rainfall, maximum temperature, minimum temperature, and streamflow respectively with the MMK test. Using the ITA method, 30 (37.5 %), 47 (58.75 %), 44 (55 %), and 34 (68 %) for rainfall, maximum temperature, minimum temperature, and streamflow were obtained respectively. This indicates that the ITA method displays stronger significant trends than the MMK method. The results benefit water resource management, drought mitigation, and sustainable agricultural planning in the basin.